2018
DOI: 10.17675/2305-6894-2018-7-4-8
|View full text |Cite
|
Sign up to set email alerts
|

Dendrimers as novel class of polymeric corrosion inhibitors: A review

Abstract: Dendrimers are a new class of highly branched, nano-sized, monodisperse macromolecules that have several fascinating physical and chemical characteristics. They are highly soluble in the polar solvents, contain several surface functionality and high surface area which makes them suitable reagents for industrial and biological applications. Recently, several dendrimers have been investigated as effective corrosion and scale inhibitors for metallic and silica corrosion using experimental and theoretical methods.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…The charge transfer resistance, R t values are calculated from the difference in impedance at lower and higher frequencies, as suggested by several authors [26][27][28][29][30][31].…”
Section: Iii6 Electrochemical Impedance Spectroscopymentioning
confidence: 99%
“…The charge transfer resistance, R t values are calculated from the difference in impedance at lower and higher frequencies, as suggested by several authors [26][27][28][29][30][31].…”
Section: Iii6 Electrochemical Impedance Spectroscopymentioning
confidence: 99%
“…Tafel slopes showed that the added inhibitor blocked the MS surface, indicating an inactivation towards corrosion and suggesting geometric blocking effect [25]. Moreover the addition of AY15 inhibitor indicates that the molecules of the inhibitor adsorbed on the MS surface [26] thereby reducing the polarization of the MS specimen i.e. reduces the conversion of the metal into metal ions.…”
Section: Tafel Plots Measurementsmentioning
confidence: 99%